A Review of Thyroid Dysfunction Due to COVID-19 - Arefzadeh, Alireza (Mini Reviews in Medicinal Chemistry, 2024)
Coronavirus disease 2019 (COVID-19) affects thyroid function. These changes are due to the direct impact of the virus on thyroid cells via angiotensin-converting–enzyme 2 (ACE2) receptors, inflammatory reaction, apoptosis in thyroid follicular cells, suppression of hypothalamus-pituitarythyroid axis, an increase in activity of adrenocortical axis, and excess cortisol release due to cytokine storm of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Euthyroid sick syndrome (ESS), thyroiditis, clinical and subclinical hypothyroidism, central hypothyroidism, exacerbation of underlying autoimmune thyroid disease, and clinical and subclinical hyperthyroidism can be associated with coronavirus. Adjuvants in coronavirus vaccines induce autoimmune/inflammatory syndrome known as vaccine adjuvants (ASIA) syndrome. Thyroiditis and Graves’ disease have been reported to be associated with ASIA syndrome after some coronavirus vaccinations. Some coronavirus medications, such as hydroxychloroquine, monoclonal antibodies, lopinavir/ritonavir, remdesivir, naproxen, anticoagulants, and glucocorticoids can also affect thyroid tests, and correct diagnosis of thyroid disorders will be more difficult. Changes in thyroid tests may be one of the most important manifestations of COVID-19. These changes can be confusing for clinicians and can lead to inappropriate diagnoses and decisions. Prospective studies should be conducted in the future to increase epidemiological and clinical data and optimize the management of thyroid dysfunctions in patients with COVID-19.
Keywords: Coronavirus disease 2019